Significant Development of the Concept of Ahl-Dhimmah on Religious Rights in Early Islamic State - Abdul Rahman, Mohamad Zaidi; Raja Sulong, Raja Hisyamudin; Md Rasip, Osman (Journal of Al-Tamaddun, 2022)
This article is to trace the problem of the right of a citizen of different religions to practice the faith in an Islamic country. This issue is not a new issue since as early as the formation of the Islamic state of Madinah, communities of different religions have also already existed. Therefore, to understand the model of managing the affairs of non -Muslim religious beliefs through the historical lens of the Prophet Muḥammad Rasūlullah (PBUH)) has become important for the ummah. The present article, using a descriptive and analytical approach and drawing upon Islamic sources, i.e. the Holy Qur’ān, the Prophetic Traditions and selected opinion of Muslim scholars to explores the conceptual framework that Muslim jurists develop their ruling with regard to issue encounter Muslim and non-Muslims affairs in the light of Fiqh al-Siyār. As a result, this study shows that the combination of the guidance of Wahy and the contract signed by the Prophet Rasūlullah (PBUH) and Ṣaḥabah with non -Muslims, especially contract of Syurūṭ ‘Umariyyah gave inspiration for jurist to provide a social conduct of religious rights for non -Muslims.